Significances of magnetic dipole flow and melting heat transfer over suspended dust particles along with carbon nanotubes - Alfannakh, Huda (Frontiers in Energy Research, 2022)
The current research letter is materialized to examine the combined effect of thermophoretic dust particle diffusion and magnetic dipole flow toward a stretchable sheet. The slip effect is used in the development of the momentum equation. Water is considered as a base fluid, and single-walled carbon nanotubes and multiwalled carbon nanotubes are nanoparticles. The aforementioned rheological model is formulated in the way of nonlinear partial differential equations (PDEs). The structure of nonlinear biformed ordinary differential equations (ODEs) is obtained from the modeled nonlinear PDEs by incorporating valid sameness transformations. The system of ODEs is then figured out by employing the tool of MATLAB function bvp4c. The significant nature of the contributing parameter for both the single-wall and multiwall cases is presented via graphs. From the results, we conclude that an impact of the melting effect, mounting of Pr, reported a thinner thermal boundary layer thickness. Furthermore, a clear rise of nanofluid temperature is noticed for the greater melting M1 parameter. The slip parameter plays a significant role in the enhancement of the velocity profile.